Cationic cellulose nanofibers from waste pulp residues and their nitrate, fluoride, sulphate and phosphate adsorption properties. (1st January 2016) - Sehaqui, Houssine; Mautner, Andreas; Perez de Larraya, Uxua; Pfenninger, Numa; Tingaut, Philippe; Zimmermann, Tanja
Highlights: Cellulose nanofibers with positive charges on their surface are prepared. These cationic nanofibers adsorb anions (e.g., nitrate and fluoride). Multivalent anions are preferably adsorbed onto the cationic nanofibers. Cationic cellulose nanofibers are processed into permeable membrane retaining nitrate. Abstract: Cationic cellulose nanofibers (CNF) having 3 different contents of positively charged quaternary ammonium groups have been prepared from waste pulp residues according to a water-based modification method involving first the etherification of the pulp with glycidyltrimethylammonium chloride followed by mechanical disintegration. The cationic nanofibers obtained were observed by scanning electron microscopy and the extent of the reaction was evaluated by conductometric titration, ζ-potential measurements, and thermogravimetric analyses. The cationic CNF had a maximum cationic charge content of 1.2 mmol g −1 and positive ζ-potential at various pH values. Sorption of negatively charged contaminants (fluoride, nitrate, phosphate and sulphate ions) and their selectivity onto cationic CNF have been evaluated. Maximum sorption of ∼0.6 mmol g −1 of these ions by CNF was achieved and selectivity adsorption studies showed that cationic CNF are more selective toward multivalent ions (PO4 3− and SO4 2− ) than monovalent ions (F − and NO3 − ). In addition, we demonstrated that cationic CNF can be manufactured into permeable membranes capable of dynamic nitrate adsorption by utilizing a simple paper-making process.